The Efficacy of Functional and Traditional Exercise on the Body Composition and Determinants of Physical Fitness of Older Women: A Randomized Crossover Trial - Antônio Gomes de Resende-Neto; José Carlos Aragão-Santos; Bruna Caroline Oliveira-Andrade; Alan Bruno Silva Vasconcelos; Clodoaldo Antônio De Sá; Felipe José Aidar; Josimari Melo DeSantana; Eduardo Lusa Cadore; Marzo Edir Da Silva-Grigoletto (Journal of Aging Research)
Aim. To analyze the efficacy of functional training (FT) and traditional training (TT) in body composition and determinants of physical fitness in older women. Methods. This is a randomized clinical trial in which participants performed two 12-week periods of different training methods, separated by eight weeks of washout. Forty-eight physically active older women (≥60 years of age) completed the intervention in three groups: (i) program that started with FT and ended with TT (FT ⟶ TT: n = 19), (ii) program that started with TT and ended with FT (TT ⟶ FT: n = 13), and (iii) stretching group (SG: n = 16). Before and after the interventions, the body composition was evaluated by bioimpedance, the physical fitness by battery of the Senior Fitness Test, and the quality of movement by Functional Movement Screen®. Results. Compared with SG, TT ⟶ FT and FT ⟶ TT promoted significant improvements in balance/agility (13.60 and 13.06%, respectively) and upper limb strength (24.91 and 16.18%). Only FT showed a statistically significant improvement in the strength of the lower limbs, cardiorespiratory capacity, and movement patterns when compared with SG considering the adaptations of methods separately. Conclusion. The programs used are equally effective in increasing physical fitness for daily activities in physically active older women, and therefore, they may be complementary to combat some of the deleterious effects of senescence.